Effect of Solvent on Gd(DOTA)– Complex Formation A Preliminary Investigation (2019)
The thermodynamic stability and kinetic inertness of gadolinium-based MRI contrast agents remains an important research topic in the field of radiological contrast agent development. In this study, the kinetics and thermodynamics of Gd3+-complex formation with the macrocyclic ligand DOTA (i.e., 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid) was investigated under aqueous (acetate buffer pH 5.8) and non-aqueous (MeOH) conditions. Using Job’s method of continuous variation, solutions were prepared of increasing mole fraction of Gd3+ relative to xylenol orange (XO, i.e., 3,3′-bis[N,N-bis(carboxymethyl)aminomethyl]-o-cresolsulfonephthalein) in MeOH, and their absorbances were measured at 582 nm.The kinetics of complex formation via ligand substitution of DOTA and DO3A (i.e., 1,4,7,10-tetraazacyclododecane-1,4,7-triacetic acid) with Gd-XO under aqueous and non-aqueous conditions were determined using UV-Vis spectrophotometry. Furthermore, the thermodynamic parameters of DOTA complexation with Gd3+ for both solvent conditions were compared by measuring the heats of injection using isothermal titration calorimetry. Results of this study demonstrate that XO forms a well-defined 1:1 stoichiometry with Gd3+ regardless of solvent polarity. Meanwhile, the rate of ligand substitution between Gd-XO and the macrocyclic ligand is effectively minimized under non-aqueous conditions (kobs, buffer= 33.9 ± 1.0 x 10–3 s–1; kobs,MeOH = 5.62 ± 2.22 x 10–3 s–1). The binding reaction of Gd3+ with DOTA has comparable negative ΔG values in the two solvents (ΔGbuffer= ‒9.28 ± 0.57 kcal/mol; ΔGMeOH = ‒8.19 ± 0.14 kcal/mol), suggesting that the reaction is equally spontaneous under both conditions. However, computation of global thermodynamic properties demonstrate that the reaction is entropically-driven in acetate buffer in comparison with MeOH where the reaction is enthalpy-driven. Finally, the nature of solvent has an effect on the metal-to-ligand stoichiometry (N) of the resulting complex, which in acetate buffer (N = 1:1) is lower than that in MeOH (N = 1:2). These results are important in the context of optimizing reaction conditions in the preparation of related MRI contrast agents.